Theatrical theme in the letters of M. Kropyvnytskyi to A. Markovych through the prism of their personal relations (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
The article examines a number of Kropivnitskyi’s letters to Antonina Markovich, which through the prism of personal relationships mailing highlights the problems in the early 1880s faced then Poltava Ukrainian amateur theater and performing arts in general. It is emphasized that in these letters the future founder of the luminaries of the theater servesasan outstanding actor and director.
Keywords: M. Kropyvnytskyi; A. Markovich; theater; repertoire; epistolary heritage